LINGUOCULTURAL CHARACTERISTICS OF PROVERBS EXPRESSING AESTHETIC VALUES IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2024)
This article describes the linguistic and cultural characteristics of proverbs in English and Uzbek languages that reflect aesthetic values and culture. By comparing Uzbek and English proverbs, we can see that the cultural characteristics of the two languages are compared to each other. In this article, comparative and contrastive analysis methods were used to compare the proverbs of these two languages. The article gives samples of many examples of folk oral creativity and compares their translations and compares culture of the two languages. As a result of comparing the language and culture of the two languages, many similarities and differences became invisible. It became obvious that the meaning of the words changed during the translation process.